Method for preparing black titanium dioxide nanosheet with exposed {001} crystal face

Through hydrothermal method and sodium borohydride calcination treatment, black titanium dioxide nanosheets with defects exposed to {001} crystal surfaces of a single anatase phase were prepared, which solved the preparation problems in the prior art and realized the material in the field of photocatalytics. Significant performance improvement.

CN119191344APending Publication Date: 2024-12-27CHENGDU UNIV

Patent Information

Application Number
CN202411121138.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-15
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The prior art is difficult to effectively prepare black titanium dioxide nanosheets with defects exposed to {001} crystal planes in a single anatase phase, limiting their application potential in the field of photocatalysis.

Method used

White titanium dioxide nanosheets were prepared by hydrothermal method, mixed with sodium borohydride and calcined. The ratio control of hydrofluoric acid and anhydrous ethanol and ultrasonic dispersion technology were used to destroy the surface of titanium dioxide by combining the strong reducing properties of sodium borohydride. structure, forming excellent exposed {001} crystal surface.

Benefits of technology

A black titanium dioxide nanosheet with excellent ultraviolet and visible light absorption properties was achieved, which showed significant photocatalytic activity in visible and sunlight, improving photocatalytic performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119191344A_ABST
    Figure CN119191344A_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing black titanium dioxide nanosheets with exposed {001} crystal faces, and relates to the technical field of photocatalytic materials.The method comprises the steps that S1, hydrofluoric acid, absolute ethyl alcohol and tetrabutyl titanate are mixed to obtain a mixed solution; s2, carrying out hydrothermal treatment on the mixed solution, separating and purifying to obtain white titanium dioxide; and S3, mixing the white titanium dioxide with sodium borohydride, grinding to obtain a mixed material, calcining the mixed material, washing, freezing and drying to obtain the black titanium dioxide nanosheet with the exposed {001} crystal face. White titanium dioxide is prepared through a hydrothermal method, then the white titanium dioxide and sodium borohydride are mixed, ground and calcined to obtain the black titanium dioxide nanosheet with the exposed {001} crystal face, and the material prepared through the method has excellent ultraviolet and visible light absorption performance and has excellent photocatalytic performance under visible light and sunlight.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of photocatalytic materials, in particular to a method for preparing black titanium dioxide nanosheets with exposed {001} crystal planes. Background Art

[0002] With the development of science and technology, photocatalytic technology driven by solar energy has potential applications and development prospects in environmental governance and energy shortages. Common titanium dioxide photocatalysts are white powders that can only utilize the ultraviolet spectrum band of natural light and be excited to generate photogenerated charges, thereby playing a role in photocatalytic oxidation or photoelectric conversion. They cannot fully utilize most of the energy in sunlight. Compared with traditional titanium dioxide nanomaterials, black titanium dioxide has a unique crystalline core / amorphous core-shell structure. Black titanium dioxide nanomaterials improve the crystal structure of titanium dioxide by introducing lattice defects, thereby optimizing its electronic energy level structure, shortening the bandgap width, and improving optical properties. Its light response range is extended from the ultraviolet region to the infrared region, making black titanium dioxide nanomaterials widely used in the fields of energy and environment.

[0003] Studies have shown that the selective exposure of special crystal planes has an effect on photocatalytic activity. The average surface energies of {001}, {100} and {101} crystal planes of different crystal planes in anatase phase are 0.90 J / m 2 , 0.44J / m 2 and 0.53 J / m 2 Therefore, preparing black TiO2 with appropriately exposed {001} crystal planes is an important means to enhance the intrinsic mechanism of photocatalysis.

[0004] The patent application with application publication number CN112516980A provides a method for preparing two-dimensional porous TiO2 nanosheets, which utilizes sol-gel method, hydrothermal synthesis, and secondary calcination of pore-forming agent to obtain titanium oxide nanosheets with two-dimensional porous structure.

[0005] A patent application with application publication number CN114477278A discloses a method for preparing black titanium oxide nanosheets using simple ball milling technology. Black titanium dioxide nanosheets are prepared using simple ball milling. The black titanium dioxide nanosheets are a mixed phase with a large number of highly active faces {001} or {100} faces, but also contain highly thermodynamically stable faces {101} faces.

[0006] The prior art does not involve a method for obtaining highly active titanium dioxide nanosheets with exposed {001} crystal planes in different proportions by hydrothermal technology, and then preparing black titanium oxide nanosheets with exposed {001} crystal planes in a single anatase phase with defects by calcination. Summary of the invention

[0007] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a method for preparing black titanium dioxide nanosheets with exposed {001} crystal planes. First, titanium dioxide nanosheets with uniform exposed {001} crystal planes are obtained by hydrothermal treatment, and then calcined to finally obtain black titanium dioxide nanosheets with exposed {001} crystal planes and defects in a single anatase phase.

[0008] To achieve the above purpose, the technical solution adopted by the present invention is as follows:

[0009] A method for preparing black titanium dioxide nanosheets with exposed {001} crystal planes, comprising:

[0010] S1, mixing hydrofluoric acid, anhydrous ethanol and tetrabutyl titanate to obtain a mixed solution;

[0011] S2, subjecting the mixed solution to hydrothermal treatment, and then separating and purifying it to obtain white titanium dioxide;

[0012] S3, mixing white titanium dioxide and sodium borohydride and grinding them to obtain a mixed material, then calcining the mixed material, washing, freeze-drying to obtain black titanium dioxide nanosheets with exposed {001} crystal planes.

[0013] Furthermore, in step S1, hydrofluoric acid, anhydrous ethanol and tetrabutyl titanate are mixed in a volume ratio of 0.4-0.8:10-30:3-7.

[0014] Furthermore, in step S1, ultrasonic dispersion is used for 10 minutes during mixing, and then stirring is carried out at a speed of 700 r / min for 30 minutes.

[0015] Furthermore, the temperature of the hydrothermal treatment in step S2 is 150-210° C., and the time is 12-24 hours.

[0016] Furthermore, in step S3, the mixing mass ratio of white titanium dioxide to sodium borohydride is 1:0.5-1.5.

[0017] Furthermore, the grinding time in step S3 is 20-40 min.

[0018] Furthermore, in step S3, the mixed material is calcined at a temperature of 300-400° C. and for a time of 15-45 min.

[0019] Furthermore, the freeze-drying time in step S3 is 6-18 hours.

[0020] A black titanium dioxide nanosheet with exposed {001} crystal plane is prepared by any of the above methods.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] (1) The present invention first uses a hydrothermal method to prepare white titanium dioxide, and then mixes the white titanium dioxide with sodium borohydride, grinds it, and calcines it to obtain black titanium dioxide nanosheets with exposed {001} crystal planes. During the hydrothermal process, the grains will grow along the crystal planes with lower surface energy, and hydrofluoric acid can selectively adhere to the {001} planes of the crystals to reduce their surface energy, so that the crystals grow along the {001} surface. During the calcination of white titanium dioxide with sodium borohydride, the strong reducing property of sodium borohydride destroys the surface structure of titanium dioxide at the crystal surface, causing oxygen to escape from the crystal lattice and generate water with reduced hydrogen, and generating oxygen vacancies on the crystal surface of titanium dioxide, ultimately obtaining black titanium dioxide nanosheets with exposed {001} crystal planes.

[0023] (2) The material prepared by the present invention has excellent ultraviolet and visible light absorption properties, and has excellent photocatalytic properties under visible light and sunlight. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 The XRD pattern of the black titanium dioxide nanosheets with exposed {001} crystal planes provided in Example 1;

[0025] Figure 2 The EPR image of the black titanium dioxide nanosheets with exposed {001} crystal planes provided in Example 1;

[0026] Figure 3 The UV-visible absorption spectrum of the black titanium dioxide nanosheets with exposed {001} crystal planes provided in Example 1;

[0027] Figure 4 TEM image of black titanium dioxide nanosheets with exposed {001} crystal planes provided in Example 1;

[0028] Figure 5 The XPS spectrum of the black titanium dioxide nanosheets with exposed {001} crystal planes provided in Example 1;

[0029] Figure 6 A characterization diagram of the visible light photocatalytic performance of the black titanium dioxide nanosheets with exposed {001} crystal planes provided in Example 1;

[0030] Figure 7 This is a characterization diagram of the solar photocatalytic performance of the black titanium dioxide nanosheets with exposed {001} crystal planes provided in Example 1. DETAILED DESCRIPTION

[0031] The present invention is further described below in conjunction with the accompanying drawings and examples, and the methods of the present invention include but are not limited to the following examples. If specific conditions are not specified in the examples, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0032] The present invention provides a method for preparing a black titanium dioxide nanosheet exposing a {001} crystal plane, comprising the following steps:

[0033] S1, mixing hydrofluoric acid, anhydrous ethanol and tetrabutyl titanate in a volume ratio of (0.4-0.8):(10-30):(3-7), performing ultrasonic dispersion for 10 minutes, and stirring at a speed of 700 r / min for 30 minutes to obtain a mixed solution;

[0034] The amount of hydrofluoric acid determines the growth trend of the crystal along the {001} crystal plane, which will affect the proportion of the final titanium dioxide exposed {001} crystal plane. If the hydrofluoric acid concentration is too high, after reaching a certain limit, other compounds such as TiOF2 will be produced, which will hinder the role of hydrofluoric acid as a capping agent; if the concentration is too low, the capping agent effect is not obvious, so the dosage is limited to a certain range. Anhydrous ethanol is used as a hydrolysis inhibitor to prevent tetrabutyl titanate from hydrolyzing before the reaction. Too much hydrolysis inhibitor will make the hydrothermal reaction time too long, and too little inhibitor will have a weaker inhibitory effect on the hydrolysis of tetrabutyl titanate. Tetrabutyl titanate is used as a titanium dioxide precursor and will affect the reaction rate to a certain extent.

[0035] S2, hydrothermally treating the mixed solution at 150-210° C. for 12-24 h, separating and purifying after the hydrothermal treatment to obtain titanium dioxide with exposed {0 01} crystal faces;

[0036] At an appropriate hydrothermal temperature, the {001} crystal plane with a high energy surface is more likely to form, while at too high or too low temperatures, the crystal is more likely to form a low energy, more stable crystal plane such as the {010} crystal plane. A shorter hydrothermal time will result in incomplete nucleation and incomplete reaction of the crystal, while a longer hydrothermal time may promote the development of certain crystal planes, thereby affecting the growth of the {001} crystal plane and the type of exposed crystal planes.

[0037] S3, mixing titanium dioxide with exposed {001} crystal plane and sodium borohydride in a mortar at a mass ratio of 1:(0.5-1.5) and grinding for 20-40 minutes to obtain a mixed material, and then calcining the mixed material at 300-400° C. for 15-45 minutes, washing and freeze-drying for 6-18 hours to obtain black titanium dioxide nanosheets with exposed {001} crystal plane;

[0038] Sodium borohydride is used as a reducing agent to reduce the black titanium dioxide nanosheets with exposed {001} crystal faces. The mass ratio of sodium borohydride to titanium dioxide determines the reduction activity during the reduction process. The appropriate mass ratio allows the particles to fully contact each other, ensuring that the reaction occurs without wasting the reducing agent. The grinding time ensures that the reducing agent is fully in contact with the black titanium dioxide nanosheets with exposed {001} crystal faces. When the reaction is completed, extending the time will not have other effects on the experimental results. If the calcination temperature is too low, the reducing activity of the reducing agent will be low and the optimal reducing activity will not be achieved. If the calcination temperature is too high, the crystal form will change to the rutile phase and the brookite phase. Therefore, the calcination temperature is limited to a certain range. A short calcination time will affect the defects on the surface of the crystal and affect the catalytic activity. If the calcination time is too long, the surface defects of the crystal will be excessive, becoming new sites for electron-hole recombination and affecting the final activity of the catalyst. Therefore, the calcination temperature is limited to a certain range. Freeze drying ensures the sublimation of water in the material, and a long drying time will not have other effects on the material.

[0039] The present invention first uses a hydrothermal method to prepare white titanium dioxide, and then mixes the white titanium dioxide with sodium borohydride, grinds it, and calcines it to obtain a black titanium dioxide nanosheet exposing the {001} crystal plane. During the hydrothermal process, the crystal grains grow along the crystal plane with lower surface energy, and hydrofluoric acid can selectively adhere to the {001} surface of the crystal to reduce its surface energy, so that the crystal grows along the {001} surface. During the calcination of the white titanium dioxide with sodium borohydride, the strong reducing property of the sodium borohydride destroys the surface structure of the titanium dioxide at the crystal surface, so that oxygen escapes from the crystal lattice and generates water with reduced hydrogen, and oxygen vacancies are generated on the crystal surface of the titanium dioxide, and finally a black titanium dioxide nanosheet exposing the {001} crystal plane is obtained.

[0040] The present invention uses white titanium dioxide with different exposed {001} crystal plane ratios as raw materials by changing the ratio of the end-capping agent (hydrofluoric acid) to the precursor (tetrabutyl titanate), and changes different ratios of the hydrolysis inhibitor (anhydrous ethanol) to explore the optimal hydrolysis inhibition ratio under hydrothermal conditions, thereby preparing titanium dioxide nanosheets with uniform exposed {001} crystal plane sizes. Then, sodium borohydride with strong reducing properties is used for calcination treatment, and the surface structure of titanium dioxide is destroyed during the calcination process, so that oxygen overflows from the lattice to form water, and oxygen vacancies are generated on the surface, and finally a single anatase phase with defects in exposed {001} crystal planes is obtained. The material prepared by this preparation method has excellent ultraviolet and visible light absorption properties, and has excellent photocatalytic properties under visible light and sunlight.

[0041] The following is a further description with reference to specific embodiments.

[0042] Example 1

[0043] This embodiment provides a method for preparing black titanium dioxide nanosheets with exposed {001} crystal planes, comprising the following steps:

[0044] 0.6 mL of hydrofluoric acid, 20 mL of anhydrous ethanol and 5 mL of tetrabutyl titanate were measured and added to a beaker and ultrasonically dispersed for 10 min, and then stirred for 30 min under a stirrer (700 r / min) to fully mix;

[0045] The mixed solution was poured into a 50 mL reactor and placed in a drying oven for hydrothermal reaction (temperature: 180°C, reaction time: 18 h). After washing and drying, white titanium dioxide with exposed {001} crystal faces was obtained.

[0046] Titanium dioxide with exposed {001} crystal face was weighed and mixed with sodium borohydride in a mass ratio of 1:1, ground in a mortar for 30 minutes, placed in a crucible, and calcined (calcination temperature: 350°C, heating rate 5°C / min, calcination time: 40 minutes). After washing and freeze-drying for 12 hours, black titanium dioxide nanosheets with exposed {001} crystal face were obtained. The obtained samples were subjected to XRD, EPR, TEM, light absorption performance, visible light photocatalytic performance, and full spectrum performance analysis. The results are shown in the attached figure. Figure 1-7 shown.

[0047] in, Figure 1 The XRD graph of the black titanium dioxide nanosheets with exposed {001} crystal planes in this embodiment shows that the peak intensity of the black titanium dioxide nanosheets with exposed {001} crystal planes prepared in this embodiment is weakened compared to the white titanium dioxide nanosheets with exposed {001} crystal planes. The decrease in peak intensity after reduction can be attributed to the modification of a disordered layer on the surface of the material. The decrease in the peak intensity of black titanium dioxide corresponds to the disordered layer in the transmission electron microscope, which is also a proof of the successful preparation of black titanium dioxide;

[0048] Figure 2 The EPR image of the black titanium dioxide nanosheets with exposed {001} crystal planes in this example shows that the white titanium dioxide nanosheets with exposed {001} crystal planes prepared in this example have obvious peaks of oxygen vacancies. The characterization of oxygen vacancies also shows that sodium borohydride successfully reduces black titanium dioxide, proving that black titanium dioxide containing oxygen vacancies was successfully prepared.

[0049] Figure 3 The UV-visible absorption spectrum of the black titanium dioxide nanosheets with exposed {001} crystal planes provided in this embodiment is shown in FIG. Figure 3 It can be seen that compared with the white titanium dioxide nanosheets exposing the {001} crystal plane and the black titanium dioxide nanosheets exposing the {001} crystal plane, the black titanium dioxide nanosheets exposing the {001} crystal plane have good ultraviolet light absorption performance.

[0050] Figure 4 The TEM image of the black titanium dioxide nanosheets with exposed {001} crystal planes provided in this embodiment is shown in FIG. Figure 4 It can be seen that the sample morphology of black titanium dioxide nanosheets is a sheet structure, d is the interplanar spacing, and the specific crystal plane can be inferred through the results of TEM and XRD. When d = 0.235nm, the (004) crystal plane of TiO2 also corresponds to the {001} crystal plane, and a certain amorphous layer appears on the surface of black titanium dioxide. Therefore, from the TEM results, it can be seen that there is an obvious disordered layer at the edge, and the thickness of the disordered layer is thinner, about 2nm.

[0051] Figure 5 The XPS spectrum of the black titanium dioxide nanosheets with exposed {001} crystal planes provided in this embodiment is shown in FIG. Figure 5 It can be seen that the valence state of the Ti element in the black titanium dioxide nanosheets exposing the {001} crystal plane is tetravalent and trivalent, which can prove that sodium borohydride effectively reduces the titanium element in titanium dioxide, proving that black titanium dioxide containing oxygen vacancies has been successfully prepared.

[0052] Figure 6 The visible light photocatalytic performance characterization diagram of the black titanium dioxide nanosheets with exposed {001} crystal planes provided in this embodiment shows clearly that the black titanium dioxide nanosheets with exposed {001} crystal planes have the performance of degrading rhodamine B (Rh B) under visible light, wherein the degradation rate of the white titanium dioxide nanosheets with exposed {001} crystal planes after 80 minutes of illumination is 43.1%, and the degradation rate of the black titanium dioxide nanosheets with exposed {001} crystal planes after illumination is 95.21%.

[0053] Figure 7 The sunlight photocatalytic performance characterization diagram of the black titanium dioxide nanosheets with exposed {001} crystal planes provided in this embodiment shows clearly that the black titanium dioxide nanosheets with exposed {001} crystal planes have the performance of degrading rhodamine B (Rh B) under visible light, wherein the degradation rate of the white titanium dioxide nanosheets with exposed {001} crystal planes after 60 minutes of illumination is 94.16%, and the degradation rate of the black titanium dioxide nanosheets with exposed {001} crystal planes after 20 minutes of illumination is 98.37%.

[0054] In summary, the black titanium dioxide nanosheets with exposed {001} crystal planes prepared in this example meet the characteristics of black titanium dioxide, and this example successfully prepared black titanium dioxide.

[0055] Example 2

[0056] This embodiment provides a method for preparing black titanium dioxide nanosheets with exposed {001} crystal planes, comprising the following steps:

[0057] 0.4 mL of hydrofluoric acid, 20 mL of anhydrous ethanol and 5 mL of tetrabutyl titanate were measured and added to a beaker and ultrasonically dispersed for 10 min, and then stirred under a stirrer (700 r / min) to mix thoroughly;

[0058] The mixed solution was poured into a 50 mL reactor and placed in a drying oven for hydrothermal reaction (temperature: 180°C, reaction time: 18 h). Titanium dioxide with exposed {001} crystal faces was obtained after washing and drying.

[0059] Titanium dioxide with exposed {001} crystal plane was weighed and mixed with sodium borohydride in a mass ratio of 1:1, ground in a mortar for 30 minutes, placed in a crucible, and calcined (calcination temperature: 350°C, heating rate 5°C / min, calcination time: 40 minutes). After washing and freeze-drying for 12 hours, black titanium dioxide nanosheets with exposed {001} crystal plane were obtained.

[0060] Example 3

[0061] This embodiment provides a method for preparing black titanium dioxide nanosheets with exposed {001} crystal planes, comprising the following steps:

[0062] 0.8 mL of hydrofluoric acid, 20 mL of anhydrous ethanol and 5 mL of tetrabutyl titanate were measured and added to a beaker and ultrasonically dispersed for 10 min, and then stirred under a stirrer (700 r / min) to mix thoroughly;

[0063] The mixed solution was poured into a 50 mL reactor and placed in a drying oven for hydrothermal reaction (temperature: 180°C, reaction time: 18 h). Titanium dioxide with exposed {001} crystal faces was obtained after washing and drying.

[0064] Titanium dioxide with exposed {001} crystal plane was weighed and mixed with sodium borohydride in a mass ratio of 1:1, ground in a mortar for 30 minutes, placed in a crucible, and calcined (calcination temperature: 350°C, heating rate 5°C / min, calcination time: 40 minutes). After washing and freeze-drying for 12 hours, black titanium dioxide nanosheets with exposed {001} crystal plane were obtained.

[0065] Example 4

[0066] This embodiment provides a method for preparing black titanium dioxide nanosheets with exposed {001} crystal planes, comprising the following steps:

[0067] 0.6 mL of hydrofluoric acid, 20 mL of anhydrous ethanol and 5 mL of tetrabutyl titanate were measured and added to a beaker and ultrasonically dispersed for 10 min, and then stirred under a stirrer (700 r / min) to mix thoroughly;

[0068] The mixed solution was poured into a 50 mL reactor and placed in a drying oven for hydrothermal reaction (temperature: 150°C, reaction time: 18 h). Titanium dioxide with exposed {001} crystal faces was obtained after washing and drying.

[0069] Titanium dioxide with exposed {001} crystal plane was weighed and mixed with sodium borohydride in a mass ratio of 1:1, ground in a mortar for 30 minutes, placed in a crucible, and calcined (calcination temperature: 350°C, heating rate 5°C / min, calcination time: 40 minutes). After washing and freeze-drying for 12 hours, black titanium dioxide nanosheets with exposed {001} crystal plane were obtained.

[0070] Example 5

[0071] This embodiment provides a method for preparing black titanium dioxide nanosheets with exposed {001} crystal planes, comprising the following steps:

[0072] 0.6 mL of hydrofluoric acid, 20 mL of anhydrous ethanol and 5 mL of tetrabutyl titanate were measured and added to a beaker and ultrasonically dispersed for 10 min, and then stirred under a stirrer (700 r / min) to mix thoroughly;

[0073] The mixed solution was poured into a 50 mL reactor and placed in a drying oven for hydrothermal reaction (temperature: 210°C, reaction time: 18 h). Titanium dioxide with exposed {001} crystal faces was obtained after washing and drying.

[0074] Titanium dioxide with exposed {001} crystal plane was weighed and mixed with sodium borohydride in a mass ratio of 1:1, ground in a mortar for 30 minutes, placed in a crucible, and calcined (calcination temperature: 350°C, heating rate 5°C / min, calcination time: 40 minutes). After washing and freeze-drying for 12 hours, black titanium dioxide nanosheets with exposed {001} crystal plane were obtained.

[0075] Example 6

[0076] This embodiment provides a method for preparing black titanium dioxide nanosheets with exposed {001} crystal planes, comprising the following steps:

[0077] 0.6 mL of hydrofluoric acid, 20 mL of anhydrous ethanol and 5 mL of tetrabutyl titanate were measured and added to a beaker and ultrasonically dispersed for 10 min, and then stirred under a stirrer (700 r / min) to mix thoroughly;

[0078] The mixed solution was poured into a 50 mL reactor and placed in a drying oven for hydrothermal reaction (temperature: 180°C, reaction time: 18 h). Titanium dioxide with exposed {001} crystal faces was obtained after washing and drying.

[0079] Titanium dioxide with exposed {001} crystal plane was weighed and mixed with sodium borohydride in a mass ratio of 1:1, ground in a mortar for 30 minutes, placed in a crucible, and calcined (calcination temperature: 300°C, heating rate 5°C / min, calcination time: 40 minutes). After washing and freeze-drying for 12 hours, black titanium dioxide nanosheets with exposed {001} crystal plane were obtained.

[0080] Example 7

[0081] This embodiment provides a method for preparing black titanium dioxide nanosheets with exposed {001} crystal planes, comprising the following steps:

[0082] 0.6 mL of hydrofluoric acid, 20 mL of anhydrous ethanol and 5 mL of tetrabutyl titanate were measured and added to a beaker and ultrasonically dispersed for 10 min, and then stirred under a stirrer (700 r / min) to mix thoroughly;

[0083] The mixed solution was poured into a 50 mL reactor and placed in a drying oven for hydrothermal reaction (temperature: 180°C, reaction time: 18 h). Titanium dioxide with exposed {001} crystal faces was obtained after washing and drying.

[0084] Titanium dioxide with exposed {001} crystal plane was weighed and mixed with sodium borohydride in a mass ratio of 1:1, ground in a mortar for 30 minutes, placed in a crucible, and calcined (calcination temperature: 400°C, heating rate 5°C / min, calcination time: 40 minutes). After washing and freeze-drying for 12 hours, black titanium dioxide nanosheets with exposed {001} crystal plane were obtained.

[0085] Example 8

[0086] This embodiment provides a method for preparing black titanium dioxide nanosheets with exposed {001} crystal planes, comprising the following steps:

[0087] 0.6 mL of hydrofluoric acid, 20 mL of anhydrous ethanol and 5 mL of tetrabutyl titanate were measured and added to a beaker and ultrasonically dispersed for 10 min, and then stirred under a stirrer (700 r / min) to mix thoroughly;

[0088] The mixed solution was poured into a 50 mL reactor and placed in a drying oven for hydrothermal reaction (temperature: 180°C, reaction time: 18 h). Titanium dioxide with exposed {001} crystal faces was obtained after washing and drying.

[0089] Titanium dioxide with exposed {001} crystal plane was weighed and mixed with sodium borohydride in a mass ratio of 1:1, ground in a mortar for 30 minutes, placed in a crucible, and calcined (calcination temperature: 350°C, heating rate 5°C / min, calcination time: 20 minutes). After washing and freeze-drying for 12 hours, black titanium dioxide nanosheets with exposed {001} crystal plane were obtained.

[0090] Example 9

[0091] This embodiment provides a method for preparing black titanium dioxide nanosheets with exposed {001} crystal planes, comprising the following steps:

[0092] 0.6 mL of hydrofluoric acid, 20 mL of anhydrous ethanol and 5 mL of tetrabutyl titanate were measured and added to a beaker and ultrasonically dispersed for 10 min, and then stirred under a stirrer (700 r / min) to mix thoroughly;

[0093] The mixed solution was poured into a 50 mL reactor and placed in a drying oven for hydrothermal reaction (temperature: 180°C, reaction time: 18 h). Titanium dioxide with exposed {001} crystal faces was obtained after washing and drying.

[0094] Titanium dioxide with exposed {001} crystal plane was weighed and mixed with sodium borohydride in a mass ratio of 1:1, ground in a mortar for 30 minutes, placed in a crucible, and calcined (calcination temperature: 350°C, heating rate 5°C / min, calcination time: 60 min). After washing and freeze-drying for 12 hours, black titanium dioxide nanosheets with exposed {001} crystal plane were obtained.

[0095] The above embodiment is only one of the preferred implementation modes of the present invention and should not be used to limit the protection scope of the present invention. Any changes or modifications that are made to the main design concept and spirit of the present invention and have no substantive significance, and the technical problems they solve are still consistent with the present invention, should be included in the protection scope of the present invention.

Claims

1. A method for preparing black titanium dioxide nanosheets with exposed {001} crystal planes, characterized in that: include: S1, mixing hydrofluoric acid, anhydrous ethanol and tetrabutyl titanate to obtain a mixed solution; S2, subjecting the mixed solution to hydrothermal treatment, separation and purification to obtain white titanium dioxide; S3, mixing white titanium dioxide and sodium borohydride and grinding them to obtain a mixed material, then calcining the mixed material, washing, freeze-drying to obtain black titanium dioxide nanosheets with exposed {001} crystal planes.

2. The method for preparing black titanium dioxide nanosheets with exposed {001} crystal planes according to claim 1, characterized in that: In step S1, hydrofluoric acid, anhydrous ethanol and tetrabutyl titanate are mixed in a volume ratio of 0.4-0.8:10-30:3-7.

3. The method for preparing black titanium dioxide nanosheets with exposed {001} crystal planes according to claim 2, characterized in that: During the mixing in step S1, ultrasonic dispersion is used for 10 minutes, and then stirring is carried out at a speed of 700 r / min for 30 minutes.

4. The method for preparing black titanium dioxide nanosheets with exposed {001} crystal planes according to claim 1, characterized in that: The temperature of the hydrothermal treatment in step S2 is 150-210° C. and the time is 12-24 hours.

5. The method for preparing black titanium dioxide nanosheets with exposed {001} crystal planes according to claim 1, 3 or 4, characterized in that: In step S3, the mixing mass ratio of white titanium dioxide to sodium borohydride is 1:0.5-1.

5.

6. The method for preparing black titanium dioxide nanosheets with exposed {001} crystal planes according to claim 5, characterized in that: The grinding time in step S3 is 20-40 min.

7. The method for preparing black titanium dioxide nanosheets with exposed {001} crystal planes according to claim 6, characterized in that: In step S3, the mixed material is calcined at a temperature of 300-400° C. and for a time of 15-45 min.

8. The method for preparing black titanium dioxide nanosheets with exposed {001} crystal planes according to claim 7, characterized in that: The freeze-drying time in step S3 is 6-18 hours.

9. A black titanium dioxide nanosheet having exposed {001} crystal planes, characterized in that: The method is prepared by any one of claims 1 to 8.

Citation Information

Patent Citations

  • Preparation method of two-dimensional porous titanium dioxide nano sheet

    CN112516980A

  • Method for preparing black titanium oxide nanosheet by using simple ball milling technology

    CN114477278A

Cited By

  • Semiconductor material polishing method based on photo-thermal coupling catalysis and application

    CN119734186A